2022
DOI: 10.1016/j.rinp.2022.105177
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control and comprehensive cost-effectiveness analysis for COVID-19

Abstract: Cost-effectiveness analysis is a mode of determining both the cost and economic health outcomes of one or more control interventions. In this work, we have formulated a non-autonomous nonlinear deterministic model to study the control of COVID-19 to unravel the cost and economic health outcomes for the autonomous nonlinear model proposed for the Kingdom of Saudi Arabia. We calculated the strength number and noticed the strength number is less than zero, meaning the proposed model does not capture multiple wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(51 citation statements)
references
References 38 publications
0
51
0
Order By: Relevance
“…A lot of mathematical models have been formulated to understand the dynamics of COVID-19 [47] , [48] , [49] , [50] , [51] . Geographical overlap of COVID-19 with other commodities such as HIV, malaria and TB is of global public health concern.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of mathematical models have been formulated to understand the dynamics of COVID-19 [47] , [48] , [49] , [50] , [51] . Geographical overlap of COVID-19 with other commodities such as HIV, malaria and TB is of global public health concern.…”
Section: Introductionmentioning
confidence: 99%
“…And as transmissibility evolves, herd immunity thresholds can be estimated by modified R 0 ( Gomes et al., 2022 ; Montalbán et al., 2020 ). Furthermore, following the results of the basic reproduction number, optimal control analyses were developed to reduce disease transmission, including co-infection ( Tchoumi et al., 2021 ), as well as the most cost-efficient measures ( Asamoah et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…And some studies have revealed that the Wuhan lockdown could benefit many people and communities, including the locals and the others (12, [20][21][22][23], and substantially suspends the national and global outbreak of COVID-19 pandemic (7,(24)(25)(26). Moreover, dynamical modeling is one of the useful tools to reveal the transmission dynamics of COVID-19 (27)(28)(29)(30). Sun et al (31) employed the dynamical model to investigate the effects of lockdown on the COVID-19 transmission in Wuhan, and found that although a later adoption of lockdown measures would reduce the scale of the epidemic in this city, there would be uncontrollable effects on other Chinese provinces and even the world.…”
Section: Introductionmentioning
confidence: 99%